Alkaloids and sulphur-containing amides from glycosmis citrifolia and glycosmis elongata - Mawardi Rahmani,; Rosmiati Muhammad Serang,; Najihah Mohd Hashim,; Mohd Aspollah Sukari,; Gwendoline C.L. EE,; Abdul Manaf Ali,; Hazar Bebe Mohd Ismail, (Universiti Kebangsaan Malaysia, 2010)
Air-dried leaves of both Glycosmis citrifolia and Glycosmis elongata collected from Bogor Botanical Garden, Indonesia were individually extracted with chloroform to give dark viscous extracts after solvent removal. Column chromatographic separation of the extract of G. citrifolia yielded 5(6)-glutene-3α-ol, two sets conformers, (E)-dambullin and (Z)-dambullin, and (E)-methyldambullin and (Z)-methyldambullin. Similar treatment of the extract of G. elongata gave skimmianine and arborinine. The structures of the compounds were elucidated based on spectroscopic data and comparison with published reports.